Orchestrating Technology and Teaching Technique for Reading of Narrative Text - Halimah, Halimah; Putri, Meilany Mutiara; Hakim, Reza Rahman; Mutiah, Siti (JEDLISH : Journal Of Education and English Language Teaching, 2022)
As an educator of this digital era, an English teacher should be able to integrate a teaching method with appropriate media to bring together in the classroom in order to gain the goal of teaching and learning effectively in an enjoyable way. Dealing with this idea, it is assumed that when the students learn in a joyful atmosphere, they can lessen the difficulties encountered during the teaching and learning process, especially in learning narrative text. Therefore, the researchers interested to investigate the implementation of the integration of technology called mind map and teaching method called suggestopedia in English narrative texts class.  To support this research, there are some related literature and related findings dealing with this research. The research is a was a descriptive qualitative with as much as  fifteen students majoring in of Pharmacy of Bhakti Medika Health Vocational School in Cianjur District West Java Province,  which were consisted of five males and ten females  students as the participants. Next, the data is gained through the observation on the reading of narrative text class. The data from those instruments is analyzed by using trough five steps; 1) preparing and organizing the data to be analyzed. In this stage the researchers prepared and organized the data, 2) reading and examining all of the facts.  This stage was used to read all of the findings form the results of observation and questionnaire, 3) coding the data. In this stage, the data findings were sorted and categorized based on the research questions, 4) transcribing the data. After selected the data based on the research question, then the data were transcribed. 5) Presenting and interpreting. over the implementation of this strategy combining with mind map as the product of technology it can be reported that the students were very happy and joyful during the teaching and learning process. The teacher let the students to playful with the narrative text. They were freedom to act out based on the characters on the text. In addition, the use of mind-map eased the teacher to deliver the material, and the students could understood the material well. Based on the finding it can be concluded that using technology integrated with suggestopedia in teaching reading of narrative text is strongly recommended.